2013
DOI: 10.1161/circinterventions.112.000278
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Endothelial Dysfunction on Residual Platelet Aggregability After Dual Antiplatelet Therapy With Aspirin and Clopidogrel in Patients With Stable Coronary Artery Disease

Abstract: Background-Dual antiplatelet therapy with aspirin and clopidogrel is widely used in patients with coronary stents. High residual platelet reactivity (high RPR) after dual antiplatelet therapy is associated with increased cardiovascular events. Endothelial function could affect platelet reactivity in vivo. We hypothesized that endothelial dysfunction could be associated with high RPR after dual antiplatelet therapy in patients with stable coronary artery disease. Methods and Results-We screened patients with st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 41 publications
1
14
0
Order By: Relevance
“…The sample size was calculated on the basis of previous reports that assessed PRU levels in Japanese CAD patients [23,24]. On the basis of the proportions of patients in our hospital, we estimated that the study subjects should include eight patients who were not treated with clopidogrel for every 10 patients treated with aspirin/clopidogrel.…”
Section: Discussionmentioning
confidence: 99%
“…The sample size was calculated on the basis of previous reports that assessed PRU levels in Japanese CAD patients [23,24]. On the basis of the proportions of patients in our hospital, we estimated that the study subjects should include eight patients who were not treated with clopidogrel for every 10 patients treated with aspirin/clopidogrel.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the RHI showed a negative correlation with the Framingham risk score and was associated with postoperative DVT independently of the Framingham risk score, DVT-related traditional risk factors, and Qthrombosis risk score. We suspect that the RHI could be associated with VTE through cardiovascular disease risk factors, including unknown factors, 8,21,44, 45 and also through intrinsic properties of the venous endothelium. It has been reported that 894 G>T polymorphism in the endothelial nitric oxide synthase gene is associated with endothelial dysfunction and the risk of VTE.…”
Section: Disclosuresmentioning
confidence: 98%
“…43 Moreover, in patients with CAD on dual antiplatelet therapy, peripheral endothelial function as assessed by RH-PAT is associated with residual platelet reactivity that may also contribute to an increased risk of in-stent thrombosis. 44 Both systemic and local endothelial dysfunction may be modifiable factors in the prevention of in-stent thrombosis, and several stent technologies are being developed in an attempt to decrease the risk of late thrombotic events, including bioabsorbable polymers, nonpolymeric stent surfaces, bioabsorbable stents, and an EPC capture stent. Possible mechanisms involved in the pathogenesis of instent restenosis include platelets and inflammatory cell activation by procedural vascular injury with subsequent local release of cytokines and growth factors, leukocyte adherence, smooth muscle cell proliferation, and extracellular matrix synthesis.…”
Section: Stent Thrombosis and In-stent Restenosismentioning
confidence: 99%